A high resilience wear-resistant sealing material and its preparation method and application
By using composite rubber, modified thermoplastic elastomer and other materials, combined with special preparation methods and vulcanization steps, the problem of difficult to take into account both the elasticity and wear resistance of the sealing material in harsh environments is solved, and the high elasticity and wear resistance are greatly improved, ensuring the long-term stability of the material.
Patent Information
- Application Number
- CN202411562715.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-05
AI Technical Summary
In harsh environments such as high temperature, high pressure, high speed friction and chemical corrosion, existing sealing materials are difficult to take into account high resilience and wear resistance, and their long-term use performance is unstable and prone to fatigue and aging.
The high-resilience wear-resistant sealing material is prepared through special preparation methods and vulcanization steps.
It has achieved a comprehensive improvement in the high resilience and wear resistance of sealing materials, stable long-term use performance, not easy to fatigue and aging, and adapt to various harsh environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-resilience wear-resistant sealing material and a preparation method and application thereof. Background Art
[0002] With the rapid development of industry, the operating conditions of various mechanical equipment are becoming more and more harsh. In many industrial fields, such as automobile manufacturing, aerospace, petrochemicals, etc., sealing materials need to withstand high temperature, high pressure, high-speed friction and erosion by various chemical substances. In these harsh environments, traditional sealing materials are often difficult to meet the requirements, and are prone to wear, aging, leakage and other problems, which affect the normal operation and service life of the equipment. For example, in automobile engines, sealing materials need to work in a high temperature and high pressure environment, while also withstanding the high-speed reciprocating motion and friction of the piston. If the resilience and wear resistance of the sealing material are insufficient, the sealing performance will be reduced, causing oil leakage, thereby affecting the performance and reliability of the engine. In the aerospace field, sealing materials need to maintain good sealing performance under extreme temperature and pressure conditions, and at the same time have the characteristics of light weight, high strength, high resilience and wear resistance to meet the high performance requirements of aircraft.
[0003] In the prior art, by adding reinforcing materials such as nanoparticles and fibers to polymer materials, the resilience, wear resistance and strength of the materials can be improved. However, there are still the following shortcomings:
[0004] (1) It is difficult to balance resilience and wear resistance: In some material systems, modifications or additives that improve resilience will have an adverse effect on wear resistance, and vice versa. For example, certain elastomers added to increase the material's resilience will make the material more susceptible to deformation or wear during friction, resulting in reduced wear resistance; while treatments that focus on improving wear resistance, such as increasing the material's hardness or adding wear-resistant particles, will reduce the material's resilience.
[0005] (2) Limited environmental adaptability: In high temperature environments, many sealing materials will experience performance degradation, such as reduced resilience, changes in hardness, and dimensional instability. For example, some rubber sealing materials are prone to softening and deformation at high temperatures, losing their sealing properties; while in low temperature environments, some materials will become brittle, resulting in a significant decrease in resilience and wear resistance.
[0006] (3) Unstable performance during long-term use: When the sealing material is subjected to compressive stress for a long time, it will produce permanent compression deformation, resulting in a decrease in resilience and affecting the sealing performance.
[0007] (4) Fatigue aging: Under repeated friction, stretching, compression, etc., the sealing material will gradually show fatigue aging phenomena, which is manifested as reduced material strength, decreased resilience, and deteriorated wear resistance.
[0008] To sum up the above problems, we need to continuously strengthen the research and development of sealing materials, while improving their high resilience and wear resistance to achieve the sealing effect required for long-term use. Summary of the invention
[0009] The problems of existing sealing materials in that the resilience and wear resistance are difficult to be comprehensively improved, the long-term performance is unstable, and they are prone to fatigue and aging are addressed. The present invention provides a high-resilience wear-resistant sealing material and a preparation method thereof. The raw materials include composite rubber, modified thermoplastic elastomer, expanded microspheres, maleic anhydride grafted polyethylene, composite wear-resistant fillers, fiber reinforcements, vulcanizers, accelerators, antioxidants, etc.; each component is used in combination according to a certain proportion, and the sealing material prepared by a special preparation method can comprehensively improve the resilience and wear resistance, and has stable long-term performance and is not prone to fatigue and aging. The specific technical scheme is as follows:
[0010] A high resilience wear-resistant sealing material, the sealing material comprising the following raw materials in parts by mass: 60 to 70 parts of composite rubber, 10 to 15 parts of modified thermoplastic elastomer, 1 to 3 parts of expanded microspheres, 2 to 5 parts of maleic anhydride grafted polyethylene, 10 to 20 parts of composite wear-resistant filler, 5 to 10 parts of fiber reinforcement, 1 to 3 parts of vulcanizer, 0.5 to 1 part of accelerator, and 0.5 to 2 parts of antioxidant.
[0011] In the above-mentioned sealing material, the preparation method of the composite rubber comprises the following steps: according to the mass ratio of nitrile rubber: silicone rubber: PVM-MA copolymer sodium ethyl ester = (6-8): (2-4): (0.02-0.05), the nitrile rubber, silicone rubber and PVM-MA copolymer sodium ethyl ester are mixed at 80°C-120°C to obtain the composite rubber.
[0012] In the above-mentioned sealing material, the preparation method of the modified thermoplastic elastomer comprises the following steps: according to the mass ratio, thermoplastic polyurethane elastomer TPU: thermoplastic polyamide elastomer TPAE: epoxy soybean oil: phenylpropyl dimethyl siloxy silicate: titanate coupling agent = (6-8): (2-4): (0.02-0.05): (0.02-0.05): (0.02-0.05), the thermoplastic polyurethane elastomer TPU, thermoplastic polyamide elastomer TPAE, epoxy soybean oil, phenylpropyl dimethyl siloxy silicate, and titanate coupling agent are blended at 210°C-230°C, extruded, cooled, and crushed to obtain a modified thermoplastic elastomer.
[0013] In the above sealing material, the model of the expanded microspheres is 180DU35, and the particle size is 28 μm to 40 μm.
[0014] In the above-mentioned sealing material, the composite wear-resistant filler includes carbon black, silicon carbide, aluminum oxide and molybdenum disulfide, and the mass ratio is carbon black: silicon carbide: aluminum oxide: molybdenum disulfide = (0.3-0.5): (5-8): (1.5-2.5): (3-5); the particle size of the carbon black is less than 1 μm; the particle size of the silicon carbide is less than 10 μm; the particle size of the aluminum oxide is less than 10 μm; the particle size of the molybdenum disulfide is less than 10 μm.
[0015] In the above sealing material, the fiber reinforcement includes glass fiber and basalt fiber, and the mass ratio is glass fiber:basalt fiber = (2-5): (5-10); the diameter of the glass fiber is 10 μm-25 μm, and the length of the glass fiber is 0.5 mm-1.5 mm; the diameter of the basalt fiber is 10 μm-25 μm, and the length of the basalt fiber is 0.5 mm-1.5 mm.
[0016] In the above sealing material, the vulcanizing agent is dicumyl peroxide DCP or 1,3-di-tert-butyl peroxycumene.
[0017] In the above sealing material, the accelerator is accelerator TMTD (tetramethylthiuram disulfide) or accelerator CZ (N-cyclohexyl-2-benzothiazole sulfenamide).
[0018] In the above sealing material, the antioxidant is antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer), antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine) or antioxidant MB (2-thiol benzimidazole).
[0019] The above-mentioned method for preparing a highly resilient wear-resistant sealing material comprises the following steps:
[0020] S1: Mix the composite wear-resistant filler and the fiber reinforcement agent uniformly according to the mass fraction to obtain a mixture A;
[0021] S2: uniformly mix the expanded microspheres, the vulcanizing agent, the accelerator and the antioxidant according to their mass fractions to obtain a mixture B;
[0022] S3: Add the composite rubber, modified thermoplastic elastomer and maleic anhydride grafted polyethylene into an internal mixer according to their mass fractions, and perform internal mixing for 5 min to 10 min at a temperature of 130° C. to 150° C. and a rotation speed of 30 r / min to 50 r / min to obtain internal mixing material C;
[0023] S4: Add mixed material A to the mixed material C, mix for 10 min to 15 min at a temperature of 60°C to 100°C and a rotation speed of 15 r / min to 30 r / min; then add mixed material B, mix for 5 min to 10 min at a temperature of 60°C to 100°C and a rotation speed of 15 r / min to 30 r / min, calender, and cut to obtain a semi-finished product D;
[0024] S5: vulcanizing the semi-finished product D in a vulcanizer to obtain a sealing material.
[0025] In S5 of the above preparation method, the parameters of the vulcanization treatment are: primary vulcanization, temperature 140°C~150°C, time 5min~10min, pressure 10MPa~15MPa; secondary vulcanization, temperature 160°C~180°C, time 10min~20min, pressure 15MPa~20MPa; tertiary vulcanization, temperature 120°C~130°C, time 20min~30min, pressure 5MPa~10MPa.
[0026] The above-mentioned high resilience wear-resistant sealing material is used to prepare sealing pads or sealing rings, and the minimum use thickness is 1.0 mm.
[0027] The high resilience wear-resistant sealing material and the preparation method thereof provided by the present invention have the following beneficial effects compared with the prior art:
[0028] 1. The raw materials of the sealing material of the present invention include composite rubber, modified thermoplastic elastomer, expanded microspheres, maleic anhydride grafted polyethylene, composite wear-resistant filler, fiber reinforcement, vulcanizer, accelerator, antioxidant, etc.; each component is used in a certain proportion, and the sealing material prepared by a special preparation method can comprehensively improve the resilience and wear resistance, has stable performance in long-term use, and is not easy to fatigue and age.
[0029] Second, the composite rubber is made of nitrile rubber, silicone rubber, and PVM-MA copolymer sodium ethyl ester mixed in a specific proportion. Compared with a single rubber, the composite rubber can withstand greater tensile, compressive and shear forces, and is not prone to breakage or deformation. Under different temperature and pressure conditions, the size of the composite rubber changes little, and the reliability of the seal can be maintained. The molecular structure and performance characteristics of different rubbers complement each other. Nitrile rubber has high strength and wear resistance, silicone rubber has good flexibility and high and low temperature resistance, and PVM-MA copolymer sodium ethyl ester can improve the adhesion and compatibility of rubber. After the three are mixed, the mechanical properties of the composite rubber are improved through synergistic effect. During the blending process, an interpenetrating network structure or other special microstructures can be formed, which enhances the mechanical properties of the rubber. It has better resilience and can quickly return to its original state after being compressed to maintain sealing performance. Even in long-term use, it can maintain good elasticity and is not prone to permanent deformation. Silicone rubber has excellent resilience. After compounding it with nitrile rubber and PVM-MA copolymer sodium ethyl ester, the resilience of the entire composite rubber can be improved. PVM-MA copolymer sodium ethyl ester can act as a plasticizer, improve the molecular chain mobility of rubber, and thus improve resilience. In the environment of friction and wear, the composite rubber can maintain sealing performance for a longer time and reduce sealing failure caused by wear. Nitrile rubber itself has a certain wear resistance. After compounding with silicone rubber and PVM-MA copolymer sodium ethyl ester, the wear resistance is improved by optimizing the molecular structure and enhancing the hardness of the material. PVM-MA copolymer sodium ethyl ester can form a protective film on the rubber surface, reduce the friction coefficient, and reduce wear. Silicone rubber has good weather resistance and anti-aging properties, and can resist the influence of ultraviolet rays, ozone and high temperature. After compounding with nitrile rubber and PVM-MA copolymer sodium ethyl ester, the anti-aging property of the entire composite rubber can be improved. PVM-MA copolymer sodium ethyl ester has the effect of anti-oxidation or anti-ultraviolet rays, which further enhances the anti-aging property of the composite rubber.
[0030] 3. Modified thermoplastic elastomers are obtained by blending thermoplastic polyurethane elastomer TPU, thermoplastic polyamide elastomer TPAE, epoxy soybean oil, phenylpropyl dimethyl siloxy silicate and titanate coupling agent in a certain proportion. Compared with simple TPU (thermoplastic polyurethane elastomer) and TPAE (thermoplastic polyamide elastomer), modified thermoplastic elastomers have improved comprehensive performance: better mechanical properties, higher resilience, toughness and wear resistance; enhanced aging resistance, can be used for a long time in harsher environments; improved processing performance, easier molding and processing. The molecular structure of epoxy soybean oil contains epoxy and fatty acid ester groups, which can interact with the molecular chains of TPU and TPAE, increase the activity of the molecular chains, thereby reducing hardness and improving flexibility; epoxy groups have certain antioxidant properties, can capture free radicals, and delay the aging process of modified thermoplastic elastomers. The molecular structure of phenylpropyl dimethyl siloxy silicate contains structures such as silicon oxygen bonds and benzene rings, which have high thermal stability and weather resistance. Silicon oxygen bonds can form a three-dimensional network structure, improving the heat resistance of the material; benzene rings can absorb ultraviolet rays and improve the weather resistance of the material. The molecular structure of the titanate coupling agent contains inorganic and organic groups, which can form chemical bonds between inorganic fillers and organic polymers, thereby improving the compatibility between the two; inorganic groups can react chemically with hydroxyl groups on the surface of the filler to form chemical bonds; organic groups can interact with polymer molecular chains to increase interfacial bonding; titanate coupling agents can also reduce the surface energy of fillers, promote the dispersion of fillers, and improve the processing performance of materials.
[0031] The addition of epoxidized soybean oil reduces the hardness of the material, making the surface stress distribution more uniform when the material is subjected to friction, reducing local stress concentration, and thus reducing the degree of wear; the lubricating effect of epoxidized soybean oil can reduce the friction between the molecular chains of the material, making the molecular chains smoother during movement, and reducing the molecular chain breakage and material wear caused by friction.
[0032] The molecular structure of phenylpropyl dimethylsiloxysilicate contains structures such as silicon oxygen bonds and benzene rings. The silicon oxygen bond has high flexibility and elasticity, and can deform and store energy when the material is subjected to external force; when the external force disappears, the silicon oxygen bond can quickly return to its original state and release energy, thereby promoting the rebound of the material. The benzene ring structure can increase the steric hindrance between molecules, making the movement of the molecular chain more free, further improving the resilience of the material. Phenylpropyl dimethylsiloxysilicate has a low surface energy and can be evenly distributed on the surface of the material to form a dense film. This film can prevent external wear particles from directly contacting the surface of the material, reducing friction and wear. The titanate coupling agent makes the interface between the filler and the matrix more tightly bonded. When the material is subjected to external force, the filler can deform synergistically with the matrix, and after the external force disappears, the filler can effectively transfer energy to the matrix, promoting the recovery of the matrix molecular chain, thereby improving the resilience of the material. Titanate coupling agent improves the interface bonding between filler and matrix. Titanate coupling agent improves the interface strength of the material, making it difficult for the filler to fall off from the matrix when the material is subjected to friction, thereby reducing the wear caused by the fall of the filler. At the same time, good interface bonding also helps to evenly disperse the filler in the matrix, avoids the agglomeration of the filler, makes the stress distribution of the material more uniform, and reduces the occurrence of local wear.
[0033] Fourth, the sealing material also adds a specific proportion of expanded microspheres, carbon black, silicon carbide, aluminum oxide, molybdenum disulfide, glass fiber and basalt fiber. When the expanded microspheres are heated to a certain temperature, the internal foaming agent produces gas to expand the microspheres, thereby occupying a certain space, filling the pores in the sealing material, and improving the sealing performance; at the same time, it can reduce the material density and reduce the weight. Carbon black particles can form physical and chemical bonds with rubber molecules, enhance the cross-linking density of rubber, thereby improving the mechanical properties and anti-aging properties of the material; enhance the strength, hardness and wear resistance of the sealing material; and improve the anti-aging performance. Silicon carbide has high hardness and high melting point, and its particles can play a role in strengthening and wear resistance in the sealing material, while maintaining stable performance under high temperature environment. Alumina has high hardness and good insulation properties, and its particles can play a role in strengthening and insulating in the sealing material, while maintaining stability at high temperatures; increase the hardness, wear resistance and high temperature resistance of the sealing material; and improve insulation performance. Molybdenum disulfide has a layered structure and can form a lubricating film on the contact surface during the friction process, reducing friction and wear, reducing the friction coefficient, and improving wear resistance and lubrication performance. Glass fiber has high strength and high modulus. It can form a reinforcing skeleton in the sealing material to improve the mechanical properties and dimensional stability of the material. Basalt fiber has high strength, high temperature resistance and good corrosion resistance. It can play a reinforcing and environmental resistance role in the sealing material, and can also improve the tensile performance and wear resistance. Carbon black mainly enhances the cross-linking density by combining with rubber molecules; hard particles such as silicon carbide and aluminum oxide improve the wear resistance and hardness of the material; glass fiber and basalt fiber form a reinforcing skeleton to improve the overall mechanical properties. Expanded microspheres reduce the material density while improving the sealing performance; other components play a role in mechanical properties, wear resistance and high temperature resistance. The functions of each component are complementary, so that the sealing material has more comprehensive performance.
[0034] 5. The present invention designs special preparation, mixing, and vulcanization steps and parameters according to the combined characteristics of the various components of the sealing material to achieve the preparation of high-performance sealing materials with good practicality. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0036] Example 1: A highly resilient wear-resistant sealing material, the sealing material comprising the following raw materials in parts by mass: 65 parts of composite rubber, 12 parts of modified thermoplastic elastomer, 2 parts of expanded microspheres, 3 parts of maleic anhydride grafted polyethylene, 15 parts of composite wear-resistant filler, 8 parts of fiber reinforcement, 2 parts of vulcanizer, 0.8 parts of accelerator, and 1.2 parts of antioxidant.
[0037] The preparation method of the composite rubber includes the following steps: mixing the nitrile rubber, silicone rubber and PVM-MA copolymer sodium ethyl ester at 100° C. to obtain the composite rubber according to the mass ratio of nitrile rubber: silicone rubber: PVM-MA copolymer sodium ethyl ester = 7:3:0.03.
[0038] Among them, the preparation method of the modified thermoplastic elastomer includes the following steps: according to the mass ratio, thermoplastic polyurethane elastomer TPU: thermoplastic polyamide elastomer TPAE: epoxy soybean oil: phenylpropyl dimethylsiloxy silicate: titanate coupling agent = 7:3:0.03:0.03:0.04, the thermoplastic polyurethane elastomer TPU, thermoplastic polyamide elastomer TPAE, epoxy soybean oil, phenylpropyl dimethylsiloxy silicate, and titanate coupling agent are blended at 220°C, extruded, cooled, and crushed to obtain a modified thermoplastic elastomer.
[0039] The composite wear-resistant filler includes carbon black, silicon carbide, aluminum oxide and molybdenum disulfide, and the mass ratio is carbon black: silicon carbide: aluminum oxide: molybdenum disulfide = 0.4:6:2:4.
[0040] The fiber reinforcement includes glass fiber and basalt fiber, and the mass ratio is glass fiber:basalt fiber=3:8.
[0041] The vulcanizing agent is dicumyl peroxide DCP, the accelerator is accelerator TMTD (tetramethylthiuram disulfide), and the antioxidant is antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer).
[0042] The above-mentioned method for preparing a highly resilient wear-resistant sealing material comprises the following steps:
[0043] S1: Mix the composite wear-resistant filler and the fiber reinforcement agent uniformly according to the mass fraction to obtain a mixture A;
[0044] S2: uniformly mix the expanded microspheres, the vulcanizing agent, the accelerator and the antioxidant according to their mass fractions to obtain a mixture B;
[0045] S3: Add the composite rubber, modified thermoplastic elastomer and maleic anhydride grafted polyethylene into an internal mixer according to their mass fractions, and perform internal mixing for 8 minutes at a temperature of 140° C. and a rotation speed of 40 r / min to obtain internal mixing material C;
[0046] S4: Add mixed material A to the mixed material C, mix for 12 minutes at a temperature of 80°C and a rotation speed of 20 r / min; then add mixed material B, mix for 8 minutes at a temperature of 80°C and a rotation speed of 20 r / min, calender, and cut to obtain a semi-finished product D;
[0047] S5: The semi-finished product D is vulcanized in a vulcanizer, and the vulcanization parameters are: primary vulcanization, temperature 145°C, time 8min, pressure 12MPa; secondary vulcanization, temperature 170°C, time 15min, pressure 18MPa; tertiary vulcanization, temperature 125°C, time 25min, pressure 8MPa; cooling, cutting, and obtaining a sealing material.
[0048] The high resilience and wear-resistant sealing material prepared in this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.0 mm.
[0049] Example 2: A highly resilient wear-resistant sealing material, the sealing material comprising the following raw materials in parts by mass: 60 parts of composite rubber, 10 parts of modified thermoplastic elastomer, 1 part of expanded microspheres, 2 parts of maleic anhydride grafted polyethylene, 10 parts of composite wear-resistant filler, 5 parts of fiber reinforcement, 1 part of vulcanizing agent, 0.5 parts of accelerator, and 0.5 parts of antioxidant.
[0050] The preparation method of the composite rubber includes the following steps: mixing the nitrile rubber, silicone rubber and PVM-MA copolymer sodium ethyl ester at 80° C. to obtain the composite rubber according to the mass ratio of nitrile rubber: silicone rubber: PVM-MA copolymer sodium ethyl ester = 6:2:0.02.
[0051] Among them, the preparation method of the modified thermoplastic elastomer includes the following steps: according to the mass ratio, thermoplastic polyurethane elastomer TPU: thermoplastic polyamide elastomer TPAE: epoxy soybean oil: phenylpropyl dimethylsiloxy silicate: titanate coupling agent = 6:2:0.02:0.02:0.03, the thermoplastic polyurethane elastomer TPU, thermoplastic polyamide elastomer TPAE, epoxy soybean oil, phenylpropyl dimethylsiloxy silicate, and titanate coupling agent are blended at 210°C, extruded, cooled, and crushed to obtain a modified thermoplastic elastomer.
[0052] The composite wear-resistant filler includes carbon black, silicon carbide, aluminum oxide and molybdenum disulfide, and the mass ratio is carbon black: silicon carbide: aluminum oxide: molybdenum disulfide = 0.3:5:1.5:3.
[0053] The fiber reinforcement includes glass fiber and basalt fiber, and the mass ratio is glass fiber:basalt fiber=2:5.
[0054] The vulcanizing agent is dicumyl peroxide DCP, the accelerator is accelerator TMTD (tetramethylthiuram disulfide), and the antioxidant is antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine).
[0055] The above-mentioned method for preparing a highly resilient wear-resistant sealing material comprises the following steps:
[0056] S1: Mix the composite wear-resistant filler and the fiber reinforcement agent uniformly according to the mass fraction to obtain a mixture A;
[0057] S2: uniformly mix the expanded microspheres, the vulcanizing agent, the accelerator and the antioxidant according to their mass fractions to obtain a mixture B;
[0058] S3: Add the composite rubber, modified thermoplastic elastomer and maleic anhydride grafted polyethylene into an internal mixer according to their mass fractions, and perform internal mixing for 5 minutes at a temperature of 130° C. and a rotation speed of 30 r / min to obtain internal mixing material C;
[0059] S4: Add mixed material A to the mixed material C, mix for 10 minutes at a temperature of 60°C and a rotation speed of 15 r / min; then add mixed material B, mix for 5 minutes at a temperature of 60°C and a rotation speed of 15 r / min, calender, and cut to obtain a semi-finished product D;
[0060] S5: vulcanizing the semi-finished product D in a vulcanizer, the vulcanization parameters are: primary vulcanization, temperature 140°C, time 5 min, pressure 10 MPa; secondary vulcanization, temperature 160°C, time 10 min, pressure 15 MPa; tertiary vulcanization, temperature 120°C, time 20 min, pressure 5 MPa; cooling, cutting, and obtaining the sealing material.
[0061] The high resilience and wear-resistant sealing material prepared in this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.0 mm.
[0062] Example 3: A highly resilient wear-resistant sealing material, the sealing material comprising the following raw materials in parts by mass: 60 parts of composite rubber, 15 parts of modified thermoplastic elastomer, 1 part of expanded microspheres, 5 parts of maleic anhydride grafted polyethylene, 10 parts of composite wear-resistant filler, 10 parts of fiber reinforcement, 1 part of vulcanizer, 1 part of accelerator, and 0.5 part of antioxidant.
[0063] The preparation method of the composite rubber includes the following steps: mixing the nitrile rubber, silicone rubber and PVM-MA copolymer sodium ethyl ester at 90° C. to obtain the composite rubber according to the mass ratio of nitrile rubber: silicone rubber: PVM-MA copolymer sodium ethyl ester = 8:2:0.05.
[0064] The preparation method of the modified thermoplastic elastomer comprises the following steps: according to the mass ratio, the thermoplastic polyurethane elastomer TPU: the thermoplastic polyamide elastomer TPAE: the epoxy soybean oil: the phenylpropyl dimethylsiloxy silicate: the titanate coupling agent = 6:4:0.02:0.05:0.02, the thermoplastic polyurethane elastomer TPU, the thermoplastic polyamide elastomer TPAE, the epoxy soybean oil, the phenylpropyl dimethylsiloxy silicate and the titanate coupling agent are blended at 230° C., extruded, cooled and crushed to obtain the modified thermoplastic elastomer.
[0065] The composite wear-resistant filler includes carbon black, silicon carbide, aluminum oxide and molybdenum disulfide, and the mass ratio is carbon black: silicon carbide: aluminum oxide: molybdenum disulfide = 0.3:8:1.5:5.
[0066] The fiber reinforcement includes glass fiber and basalt fiber, and the mass ratio is glass fiber:basalt fiber=2.5:10.
[0067] The curing agent is 1,3-di-tert-butyl peroxyisopropylbenzene. The accelerator is accelerator CZ (N-cyclohexyl-2-benzothiazolesulfonamide). The antioxidant is antioxidant 4010NA (N-isopropyl-N'-phenyl-p-phenylenediamine).
[0068] The above-mentioned method for preparing a highly resilient wear-resistant sealing material comprises the following steps:
[0069] S1: Mix the composite wear-resistant filler and the fiber reinforcement agent uniformly according to the mass fraction to obtain a mixture A;
[0070] S2: uniformly mix the expanded microspheres, the vulcanizing agent, the accelerator and the antioxidant according to their mass fractions to obtain a mixture B;
[0071] S3: Add the composite rubber, modified thermoplastic elastomer and maleic anhydride grafted polyethylene into an internal mixer according to their mass fractions, and perform internal mixing for 5 minutes at a temperature of 130° C. and a rotation speed of 50 r / min to obtain internal mixing material C;
[0072] S4: Add mixed material A to the mixed material C, mix for 15 minutes at a temperature of 100°C and a rotation speed of 15 r / min; then add mixed material B, mix for 5 minutes at a temperature of 60°C and a rotation speed of 30 r / min, calender, and cut to obtain a semi-finished product D;
[0073] S5: vulcanizing the semi-finished product D in a vulcanizer, the vulcanization parameters are: primary vulcanization, temperature 150°C, time 5min, pressure 15MPa; secondary vulcanization, temperature 160°C, time 20min, pressure 15MPa; tertiary vulcanization, temperature 130°C, time 20min, pressure 10MPa; cooling, cutting, and obtaining the sealing material.
[0074] The high resilience and wear-resistant sealing material prepared in this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.0 mm.
[0075] Example 4: A highly resilient wear-resistant sealing material, the sealing material comprising the following raw materials in parts by mass: 70 parts of composite rubber, 15 parts of modified thermoplastic elastomer, 3 parts of expanded microspheres, 5 parts of maleic anhydride grafted polyethylene, 20 parts of composite wear-resistant filler, 10 parts of fiber reinforcement, 3 parts of vulcanizer, 1 part of accelerator, and 2 parts of antioxidant.
[0076] The preparation method of the composite rubber includes the following steps: mixing the nitrile rubber, silicone rubber and PVM-MA copolymer sodium ethyl ester at 110° C. to obtain the composite rubber according to the mass ratio of nitrile rubber: silicone rubber: PVM-MA copolymer sodium ethyl ester = 8:4:0.05.
[0077] Among them, the preparation method of the modified thermoplastic elastomer includes the following steps: according to the mass ratio, thermoplastic polyurethane elastomer TPU: thermoplastic polyamide elastomer TPAE: epoxy soybean oil: phenylpropyl dimethylsiloxy silicate: titanate coupling agent = 8:4:0.05:0.05:0.05, the thermoplastic polyurethane elastomer TPU, thermoplastic polyamide elastomer TPAE, epoxy soybean oil, phenylpropyl dimethylsiloxy silicate, and titanate coupling agent are blended at 230°C, extruded, cooled, and crushed to obtain a modified thermoplastic elastomer.
[0078] The composite wear-resistant filler includes carbon black, silicon carbide, aluminum oxide and molybdenum disulfide, and the mass ratio is carbon black: silicon carbide: aluminum oxide: molybdenum disulfide = 0.5:8:2.5:5.
[0079] The fiber reinforcement includes glass fiber and basalt fiber, and the mass ratio is glass fiber:basalt fiber=5:9.
[0080] The curing agent is 1,3-di-tert-butyl peroxyisopropylbenzene, the accelerator is accelerator CZ (N-cyclohexyl-2-benzothiazole sulfenamide), and the antioxidant is antioxidant MB (2-mercaptobenzimidazole).
[0081] The above-mentioned method for preparing a highly resilient wear-resistant sealing material comprises the following steps:
[0082] S1: Mix the composite wear-resistant filler and the fiber reinforcement agent uniformly according to the mass fraction to obtain a mixture A;
[0083] S2: uniformly mix the expanded microspheres, the vulcanizing agent, the accelerator and the antioxidant according to their mass fractions to obtain a mixture B;
[0084] S3: Add the composite rubber, modified thermoplastic elastomer and maleic anhydride grafted polyethylene into an internal mixer according to their mass fractions, and perform internal mixing for 10 minutes at a temperature of 150° C. and a rotation speed of 50 r / min to obtain internal mixing material C;
[0085] S4: Adding mixed material A to the mixed material C, mixing for 15 minutes at a temperature of 100°C and a rotation speed of 30 r / min; then adding mixed material B, mixing for 10 minutes at a temperature of 100°C and a rotation speed of 30 r / min, calendering, cutting, and obtaining a semi-finished product D;
[0086] S5: vulcanizing the semi-finished product D in a vulcanizer, the vulcanization parameters are: primary vulcanization, temperature 150°C, time 10min, pressure 15MPa; secondary vulcanization, temperature 180°C, time 20min, pressure 20MPa; tertiary vulcanization, temperature 130°C, time 30min, pressure 10MPa; cooling, cutting, and obtaining the sealing material.
[0087] The high resilience and wear-resistant sealing material prepared in this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.0 mm.
[0088] Example 5: A highly resilient wear-resistant sealing material, the sealing material comprising the following raw materials in parts by mass: 70 parts of composite rubber, 10 parts of modified thermoplastic elastomer, 3 parts of expanded microspheres, 2 parts of maleic anhydride grafted polyethylene, 20 parts of composite wear-resistant filler, 5 parts of fiber reinforcement, 3 parts of vulcanizer, 0.5 parts of accelerator, and 2 parts of antioxidant.
[0089] The preparation method of the composite rubber includes the following steps: mixing the nitrile rubber, silicone rubber and PVM-MA copolymer sodium ethyl ester at 120° C. to obtain the composite rubber according to the mass ratio of nitrile rubber: silicone rubber: PVM-MA copolymer sodium ethyl ester = 6:4:0.02.
[0090] The preparation method of the modified thermoplastic elastomer comprises the following steps: according to the mass ratio, the thermoplastic polyurethane elastomer TPU: the thermoplastic polyamide elastomer TPAE: the epoxy soybean oil: the phenylpropyl dimethylsiloxy silicate: the titanate coupling agent = 8:2:0.05:0.02:0.05, the thermoplastic polyurethane elastomer TPU, the thermoplastic polyamide elastomer TPAE, the epoxy soybean oil, the phenylpropyl dimethylsiloxy silicate and the titanate coupling agent are blended at 210°C, extruded, cooled and crushed to obtain the modified thermoplastic elastomer.
[0091] The composite wear-resistant filler includes carbon black, silicon carbide, aluminum oxide and molybdenum disulfide, and the mass ratio is carbon black: silicon carbide: aluminum oxide: molybdenum disulfide = 0.5:5:2.5:3.
[0092] The fiber reinforcement includes glass fiber and basalt fiber, and the mass ratio is glass fiber:basalt fiber=5:6.
[0093] The vulcanizing agent is 1,3-di-tert-butyl peroxyisopropylbenzene, the accelerator is accelerator TMTD (tetramethylthiuram disulfide), and the antioxidant is antioxidant MB (2-mercaptobenzimidazole).
[0094] The above-mentioned method for preparing a highly resilient wear-resistant sealing material comprises the following steps:
[0095] S1: Mix the composite wear-resistant filler and the fiber reinforcement agent uniformly according to the mass fraction to obtain a mixture A;
[0096] S2: uniformly mix the expanded microspheres, the vulcanizing agent, the accelerator and the antioxidant according to their mass fractions to obtain a mixture B;
[0097] S3: Add the composite rubber, modified thermoplastic elastomer and maleic anhydride grafted polyethylene into an internal mixer according to their mass fractions, and perform internal mixing for 10 minutes at a temperature of 150° C. and a rotation speed of 30 r / min to obtain internal mixing material C;
[0098] S4: Add mixed material A to the mixed material C, mix for 10 min at a temperature of 60°C and a rotation speed of 30 r / min; then add mixed material B, mix for 10 min at a temperature of 100°C and a rotation speed of 15 r / min, calender, and cut to obtain a semi-finished product D;
[0099] S5: The semi-finished product D is vulcanized in a vulcanizer, and the vulcanization parameters are: primary vulcanization, temperature 140°C, time 10min, pressure 10MPa; secondary vulcanization, temperature 180°C, time 10min, pressure 20MPa; tertiary vulcanization, temperature 120°C, time 30min, pressure 5MPa; cooling, cutting, and obtaining a sealing material.
[0100] The high resilience and wear-resistant sealing material prepared in this embodiment is used to prepare sealing gaskets or sealing rings, and the minimum use thickness is 1.0 mm.
[0101] In the above embodiments: the model of the expanded microspheres used is 180DU35, with a particle size range of 28μm to 40μm, from Boliken, USA. The particle size of the carbon black used is less than 1μm; the particle size of silicon carbide is less than 10μm; the particle size of aluminum oxide is less than 10μm; the particle size of molybdenum disulfide is less than 10μm. The diameter range of the glass fiber used is 10μm to 25μm, and the length range of the glass fiber is 0.5mm to 1.5mm; the diameter range of the basalt fiber is 10μm to 25μm, and the length range of the basalt fiber is 0.5mm to 1.5mm. The PVM-MA copolymer sodium ethyl ester used is from Hangzhou Oushi Technology Co., Ltd. The model of the thermoplastic polyurethane elastomer TPU is 385E, from Shanghai Fengmeite Plastic Co., Ltd. The model of the thermoplastic polyamide elastomer TPAE is nylon 66 series 1039, from Suzhou Taoye Plastic Co., Ltd. The model of titanate coupling agent is NDZ-201, Dongguan Kangjin New Material Technology Co., Ltd.
[0102] Comparative Example 1
[0103] In the preparation method of the composite rubber, no PVM-MA copolymer sodium ethyl ester is added; other parameters and methods are the same as in Example 1.
[0104] Comparative Example 2
[0105] In the preparation method of the modified thermoplastic elastomer, no epoxy soybean oil is added; other parameters and methods are the same as in Example 1.
[0106] Comparative Example 3
[0107] In the preparation method of the modified thermoplastic elastomer, no phenylpropyldimethylsiloxysilicate is added; other parameters and methods are the same as in Example 1.
[0108] Comparative Example 4
[0109] In the preparation method of the modified thermoplastic elastomer, no titanate coupling agent is added; other parameters and methods are the same as in Example 1.
[0110] Comparative Example 5
[0111] In the preparation method of the modified thermoplastic elastomer, epoxy soybean oil, phenylpropyl dimethylsiloxysilicate and titanate coupling agent are not added at the same time; other parameters and methods are the same as in Example 1.
[0112] Comparative Example 6
[0113] No basalt fiber is added to the fiber reinforcement, and all glass fibers are used; other parameters and methods are the same as in Example 1.
[0114] Comparative Example 7
[0115] No expanded microspheres are added to the sealing material; other parameters and methods are the same as in Example 1.
[0116] Comparative Example 8
[0117] The modified thermoplastic elastomer is not prepared by pre-modification, that is, the thermoplastic polyurethane elastomer TPU, the thermoplastic polyamide elastomer TPAE, the epoxy soybean oil, the phenylpropyl dimethylsiloxy silicate, and the titanate coupling agent are directly added to the internal mixer in S3 according to the mass fraction; other parameters and methods are the same as in Example 1.
[0118] The performance of the sealing material samples prepared in the above embodiments and comparative examples was tested.
[0119] 1. Take the high resilience wear-resistant sealing materials prepared in each embodiment and each comparative example respectively, refer to GB / T531.1, GB / T528, GB / T529, GB / T1683, GB / T15256 and other testing specifications, prepare corresponding specimens with different testing requirements, and carry out performance tests according to the testing method of vulcanized rubber. The results are shown in Table 1 below.
[0120] Table 1 Conventional performance test results
[0121]
[0122] From the above results, it can be seen that there is no significant difference in hardness, tensile strength at break, tear strength, oil absorption at 80°C, water absorption at 80°C and brittle temperature between the embodiments and the comparative examples. The elongation at break of the embodiment is not less than 403%, and the compression permanent deformation rate (120°C·80h) is not more than 12%, indicating that the sealing material has good resilience and can better adapt to different deformation and stress conditions; from the results of comparative example 1, it can be seen that without adding sodium ethyl ester of PVM-MA copolymer to the composite rubber, the elongation at break is slightly reduced, the compression permanent deformation rate (120°C·80h) is slightly increased, and the resilience of the sealing material is reduced; from the results of comparative examples 2 to 4, it can be seen that without adding epoxy soybean oil, phenylpropyl dimethylsiloxy silicate or titanate coupling agent to the modified thermoplastic elastomer, the elongation at break and the compression permanent deformation rate (120°C·80h) will be affected. h), which reduces the resilience of the sealing material; from the results of Comparative Example 5, it can be seen that when epoxy soybean oil, phenylpropyl dimethylsiloxysilicate and titanate coupling agent are not added to the modified thermoplastic elastomer at the same time, the elongation at break is reduced to 270%, the compression permanent deformation rate (120℃·80h) is increased to 17.5%, and the resilience of the sealing material is greatly reduced, indicating that the several materials have a synergistic effect, and the lack of them has a greater impact on the resilience of the sealing material; from the results of Comparative Examples 6 to 7, it can be seen that when basalt fiber is not added to the fiber reinforcement or expanded microspheres are not added to the sealing material, the compression permanent deformation rate (120℃·80h) increases, and the resilience of the sealing material decreases; from the results of Comparative Example 8, it can be seen that the modified thermoplastic elastomer is not prepared in advance, the compression permanent deformation rate (120℃·80h) increases, and the resilience of the sealing material decreases.
[0123] 2. Resilience test:
[0124] The high resilience wear-resistant sealing materials prepared in each embodiment and each comparative example were respectively taken, and the compression resilience of the high resilience wear-resistant sealing materials was tested according to the test method in GB / T 7759.1-2015 "Determination of compression permanent deformation of vulcanized rubber or thermoplastic rubber Part 1: Under normal and high temperature conditions". Under normal temperature conditions, 15% compression was applied, and each group was tested 3 times, and the average value was taken. The results are shown in Table 2 below.
[0125] Table 2 Resilience test results
[0126]
[0127] From the above results, it can be seen that the 15% compression deformation rebound rate of Examples 1 to 5 can reach more than 83%, indicating that the resilience of the sealing material is good. From the results of Comparative Example 1, it can be seen that without adding sodium ethyl ester of PVM-MA copolymer to the composite rubber, the 15% compression deformation rebound rate is reduced, which has little effect on the resilience of the sealing material; from the results of Comparative Examples 2 to 4, it can be seen that without adding epoxy soybean oil, phenylpropyl dimethylsiloxysilicate or titanate coupling agent to the modified thermoplastic elastomer, the 15% compression deformation rebound rate will be reduced, so that the resilience of the sealing material is slightly reduced; from the results of Comparative Example 5, it can be seen that without adding epoxy soybean oil, phenylpropyl dimethylsiloxysilicate or titanate coupling agent to the modified thermoplastic elastomer, the 15% compression deformation rebound rate will be reduced, so that the resilience of the sealing material is slightly reduced. By adding epoxy soybean oil, phenylpropyl dimethylsiloxysilicate and titanate coupling agent, the 15% compression deformation rebound rate is reduced to 68%, and the resilience of the sealing material is greatly reduced, indicating that the several materials have a synergistic effect. At the same time, the lack of them has a greater impact on the resilience of the sealing material; from the results of Comparative Examples 6 to 7, it can be seen that without adding basalt fiber to the fiber reinforcement or expanding microspheres to the sealing material, the 15% compression deformation rebound rate is reduced, and the impact on the resilience performance of the sealing material is small; from the results of Comparative Example 8, it can be seen that the modified thermoplastic elastomer is not prepared in advance, the 15% compression deformation rebound rate is reduced, and the resilience of the sealing material is reduced.
[0128] 3. Wear resistance test:
[0129] The high resilience wear-resistant sealing materials prepared in each embodiment and each comparative example were respectively taken, and the wear resistance of the high resilience wear-resistant sealing materials was tested according to the test method in "GB / T 9867-2008 Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method)", and the wear loss (g / cm 2 ), each group was measured 3 times in parallel and the average value was taken. The smaller the wear amount per unit area, the better the wear resistance. The results are shown in Table 3 below.
[0130] Table 3 Wear test results
[0131]
[0132] From the above results, it can be seen that the maximum wear loss of Examples 1 to 5 is only 0.16 g / cm 2 , indicating that the sealing material has good wear resistance. From Comparative Example 1, it can be seen that without adding PVM-MA copolymer sodium ethyl ester to the composite rubber, the wear loss increases to 0.22g / cm 2, the wear resistance of the sealing material is significantly weakened; from Comparative Examples 2 to 4, it can be seen that when epoxy soybean oil, phenylpropyl dimethyl siloxy silicate or titanate coupling agent is not added to the modified thermoplastic elastomer, the wear amount is slightly increased, and the wear resistance of the sealing material is weakened; from Comparative Example 5, it can be seen that epoxy soybean oil, phenylpropyl dimethyl siloxy silicate and titanate coupling agent are not added to the modified thermoplastic elastomer at the same time, the wear amount is slightly increased, and the wear resistance of the sealing material is weakened, indicating that the effects of several materials on the wear resistance of the sealing material have no superimposed synergistic effect; from Comparative Example 6, it can be seen that when basalt fiber is not added to the fiber reinforcement, the wear amount increases to 0.28g / cm 2 , the wear resistance of the sealing material is significantly weakened; from Comparative Example 7, it can be seen that without adding expanded microspheres to the sealing material, the wear amount increases and the wear resistance of the sealing material weakens; from Comparative Example 8, it can be seen that without pre-modification of the modified thermoplastic elastomer, the wear amount increases and the wear resistance of the sealing material weakens.
Claims
1. A highly resilient wear-resistant sealing material, characterized in that: The sealing material includes the following raw materials in parts by mass: 60 to 70 parts of composite rubber, 10 to 15 parts of modified thermoplastic elastomer, 1 to 3 parts of expanded microspheres, 2 to 5 parts of maleic anhydride grafted polyethylene, 10 to 20 parts of composite wear-resistant fillers, 5 to 10 parts of fiber reinforcement, 1 to 3 parts of vulcanizing agent, 0.5 to 1 part of accelerator, and 0.5 to 2 parts of antioxidant; The preparation method of the composite rubber comprises the following steps: mixing the nitrile rubber, silicone rubber and PVM-MA copolymer sodium ethyl ester at 80° C. to 120° C. to obtain the composite rubber according to the mass ratio of nitrile rubber: silicone rubber: PVM-MA copolymer sodium ethyl ester = (6 to 8): (2 to 4): (0.02 to 0.05); The preparation method of the modified thermoplastic elastomer comprises the following steps: according to the mass ratio of thermoplastic polyurethane elastomer TPU: thermoplastic polyamide elastomer TPAE: epoxy soybean oil: phenylpropyl dimethyl siloxy silicate: titanate coupling agent = (6-8): (2-4): (0.02-0.05): (0.02-0.05): (0.02-0.05), the thermoplastic polyurethane elastomer TPU, the thermoplastic polyamide elastomer TPAE, epoxy soybean oil, phenylpropyl dimethyl siloxy silicate and the titanate coupling agent are blended at 210° C. to 230° C., extruded, cooled and crushed to obtain the modified thermoplastic elastomer; The composite wear-resistant filler comprises carbon black, silicon carbide, aluminum oxide and molybdenum disulfide, and the mass ratio is carbon black: silicon carbide: aluminum oxide: molybdenum disulfide = (0.3-0.5): (5-8): (1.5-2.5): (3-5); the particle size of the carbon black is less than 1 μm; the particle size of the silicon carbide is less than 10 μm; the particle size of the aluminum oxide is less than 10 μm; the particle size of the molybdenum disulfide is less than 10 μm; The fiber reinforcement comprises glass fiber and basalt fiber, and the mass ratio is glass fiber:basalt fiber=(2-5):(5-10); the diameter of the glass fiber is 10 μm-25 μm, and the length of the glass fiber is 0.5 mm-1.5 mm; the diameter of the basalt fiber is 10 μm-25 μm, and the length of the basalt fiber is 0.5 mm-1.5 mm.
2. A high resilience wear-resistant sealing material according to claim 1, characterized in that: The model of the expanded microspheres is 180DU35, and the particle size is 28 μm to 40 μm.
3. The high resilience wear-resistant sealing material according to claim 1, characterized in that: The vulcanizing agent is dicumyl peroxide DCP or 1,3-di-tert-butyl peroxycumene; the accelerator is accelerator TMTD or accelerator CZ; the antioxidant is antioxidant RD, antioxidant 4010NA or antioxidant MB.
4. A method for preparing a high resilience wear-resistant sealing material, used for preparing the high resilience wear-resistant sealing material according to claim 1, characterized in that: The preparation method comprises the following steps: S1: Mix the composite wear-resistant filler and the fiber reinforcement agent uniformly according to the mass fraction to obtain a mixture A; S2: uniformly mix the expanded microspheres, the vulcanizing agent, the accelerator and the antioxidant according to their mass fractions to obtain a mixture B; S3: Add the composite rubber, modified thermoplastic elastomer and maleic anhydride grafted polyethylene into an internal mixer according to their mass fractions, and perform internal mixing for 5 min to 10 min at a temperature of 130° C. to 150° C. and a rotation speed of 30 r / min to 50 r / min to obtain internal mixing material C; S4: Add mixed material A to the mixed material C, mix for 10 min to 15 min at a temperature of 60°C to 100°C and a rotation speed of 15 r / min to 30 r / min; then add mixed material B, mix for 5 min to 10 min at a temperature of 60°C to 100°C and a rotation speed of 15 r / min to 30 r / min, calender, and cut to obtain a semi-finished product D; S5: vulcanizing the semi-finished product D in a vulcanizer to obtain a sealing material.
5. The method for preparing a high resilience wear-resistant sealing material according to claim 4, characterized in that: In S5, the parameters of the vulcanization treatment are: primary vulcanization, temperature 140°C to 150°C, time 5min to 10min, pressure 10MPa to 15MPa; secondary vulcanization, temperature 160°C to 180°C, time 10min to 20min, pressure 15MPa to 20MPa; tertiary vulcanization, temperature 120°C to 130°C, time 20min to 30min, pressure 5MPa to 10MPa.
6. The method for preparing a high resilience wear-resistant sealing material according to claim 4, characterized in that: The sealing material is used to prepare a sealing gasket or a sealing ring, and the minimum use thickness is 1.0 mm.
Citation Information
Patent Citations
Heat-expandable microsphere and use thereof
CN112424309A
High-strength and high-elasticity rubber composite material for sealing ring and preparation method thereof
CN118599197A